Smallholder farmers’ participation in profitable value chains and contract farming: Evidence from irrigated agriculture in Egypt - Tabe-Ojong, Martin Paul Jr.; Abay, Kibrom A. (International Food Policy Research Institute, 2023)
The participation of smallholder farmers in high-value and profitable value chains as well as contract farming remains low in Africa. This paper aims to identify observable and unobservable constraints that explain joint participation in profitable value chains and contract farming. We use a multivariate probit model to estimate potential complementarities between the cultivation of these various value chains (vegetables, fruits, spices, herbs, and cereals), and participation in contract farming. We identify several important observable factors that reinforce and hence limit smallholders’ participation in both low and highvalue chains as well as contract farming. For example, we find suggestive evidence that mallholders in Egypt face a trade-off between ensuring food security to their households and maximizing profit, and land plays a major factor in moderating this trade-off. We find that farmers with limited land resources are more likely to devote a larger share of their land to low-value crops such as cereals while this pattern weakens with increasing land size and slightly reverses for high-value crops such as spices and herbs. This suggests until some level of land resources, food security goals may dominate profit motives while this reverses after ensuring that food security goals are achieved. Younger and wealthier farmers are more likely to participate in the cultivation of high-value crops such as spices and herbs as well as contract farming. We also document strong complementarities between participation in high-value value chains and contract farming. Particularly, farmers who cultivate high-value crops are more likely to be engaged in contract farming. Intuitively, this implies that addressing smallholders’ binding constraints, including risk and access to land, can encourage participation in profitable value chains and contract farming. Our findings offer suggestive evidence that may serve in targeting smallholders to join profitable value chains in Egypt and other comparable contexts.